Improvement of Learning Outcomes Using Interactive Media in SDN 1 Sendang - Asmuni Asmuni (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This research was carried out with the aim of improving student learning outcomes in online learning with interactive media for grade 4 SD Negeri 1 Sendang students. This type of research is classroom action research (PTK). The subjects were grade 4 students of SD Negeri 1 Sendang, Todanan District, Blora Regency, totaling 15 students. The design of CAR uses interactive media to improve student learning outcomes in Thematic Subject 5 for grade 4 students of SD Negeri 1 Sendang. Data collection techniques using observation and tests. The data analysis used descriptive quantitative and qualitative statistics. The results showed an increase in student learning outcomes, this can be seen from the results of the evaluation of the pre-action activities and each cycle, namely the pre-action by 33.3%., In the first cycle it was 53.3%, in the second cycle it was 66%., while the third cycle was 87%. Thus it can be concluded that the use of interactive media can improve student learning outcomes in thematic learning.